The effects of different extenders and myo-inositol on post-thaw quality of ram semen - Kulaksiz, Recai; Bucak, Mustafa Numan; Akçay, Ergun; SakIn, Fatih; Daşkin, Ali; AteşşahIn, Ahmet (Veteriner Fakultesi Dergisi, 2011)
The study was conducted to evaluate the effects of different extenders and inositol additions on post-thaw semen quality, lipid peroxidation (LPO) and antioxidant activities. Semen was collected from four Karayaka rams from by artificial vagina three times a week. Semen samples showing normospermy quality were pooled. The pooled semen samples were extended in three extenders (Tris, T-, skimmed milk, M- and sodium citrate, NaC) with myo-inositol at two different doses (5 mM, 10 mM) and no antioxidant (control). Nine experimental groups were assigned as follows: T-5I, T-10I, T (control); M-5I, M-10I, M (control); Na-5I, Na-10I, NaC (control). Straws containing extended semen were equilibrated at 4°C for 2 h, frozen in vapor of (15 min at-120°C) liquid nitrogen and stored in liquid nitrogen. Frozen semen was thawed in a water bath at 37°C for 30 seconds. The use of all the extenders supplemented with different doses of myo-inositol did not lead to any significant improvement in microscopic sperm and oxidative stress parameters (P>0.05). Extenders of T and M resulted in higher sperm motility (50.00±2.24% and 55.00±0.42%) and HOST (49.00 3.32% and 48.17±2.97%) rates, compared to NaC (37.00±3.74% and 31.80±2.96%, P<0.01), following the freeze/thawing process. Extenders supplementated with myo-inositol not significantly affect malondialdehyde (MDA) levels and activities of catalase (CAT), superoxide dismutase (SOD), glutathione (GSH) and glutathione peroxidase (GSH-PX) in comparison to the control groups (P>0.05), except for MDA level of T extender containing 10 mM inositol. MDA level was found lower (1.22±0.07 nmol/ml) in T than those of the M and NaC (P<0.05). For GSH and GSH-PX activities, T and NaC gave the higher values, compared to M, following the freeze/thawing process (P<0.01).
Koç spermasının çözüm sonu kalitesi üzerine farklı sulandırıcıların ve myo-i?nositolün etkileri
Keywords: Antioxidant activities; Cryopreservation; Inositol; Ram semen; Semen parameters